The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Indonesia, with the description of three new species - Loktionov, Valery M.; Lelej, Arkady S. (Zootaxa, 2019)
Four species of the genus Telostholus Haupt, 1929 are reported from Indonesia, three of them are described and illustrated as new species: T. celebes Loktionov & Lelej, sp. nov. (Sulawesi), T. rinjani Loktionov & Lelej, sp. nov. (Lombok) and T. sulawesi Loktionov & Lelej, sp. nov. (Sulawesi). The genus Telostholus is newly recorded from the islands of Sulawesi and Lombok. A key to the Indonesian species is given for females.